Katy's debate - Sawyer, Kim Vogel (Grand Rapids, Mich. : Zondervan, 2010)
Katy, a Mennonite teenager attending secular high school, joins the debate team, and tries to keep her father from remarrying so that she does not have to adjust to having a stepmother.
Young Adult
Keywords: Mennonites -- Juvenile fiction; Christian life -- Juvenile fiction; Debates and debating -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Stepmothers -- Juvenile fiction; Kansas -- Juvenile fiction